If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8c + -4 = 2 + -4c Reorder the terms: -4 + 8c = 2 + -4c Solving -4 + 8c = 2 + -4c Solving for variable 'c'. Move all terms containing c to the left, all other terms to the right. Add '4c' to each side of the equation. -4 + 8c + 4c = 2 + -4c + 4c Combine like terms: 8c + 4c = 12c -4 + 12c = 2 + -4c + 4c Combine like terms: -4c + 4c = 0 -4 + 12c = 2 + 0 -4 + 12c = 2 Add '4' to each side of the equation. -4 + 4 + 12c = 2 + 4 Combine like terms: -4 + 4 = 0 0 + 12c = 2 + 4 12c = 2 + 4 Combine like terms: 2 + 4 = 6 12c = 6 Divide each side by '12'. c = 0.5 Simplifying c = 0.5
| (x+2)(2x+1)=(x+6)(2x+3) | | 18w=234 | | -27=-7w+4(w-6) | | 4y^2-8y+9=0 | | 14-(5x-6)=-6(x+1)-5 | | (x+1)(x-3)=4 | | [x]=7 | | 4(2x+3)=6(x+3) | | 8=2v+6 | | .5(1-2.5y)+1.25y=.5 | | -17=n/4-13 | | .8(3v-2w)+.2(7v-2w)= | | 3y=7+5 | | -9y-3=-8y-7 | | 11x+8=4x-6 | | 5w^2+41w+42=0 | | n+15=30 | | 8+13=-3(7x-7) | | 5(5t-2)=-36 | | 9x+1=46 | | -4(y-3)=6y-7 | | m/6=-9 | | .5x+1.25y=.5 | | n+15=23 | | 8+13=3(7x-7) | | -(3x-5y)-8(2x+y)= | | -2.35+6.75=-2.18 | | (a^3b)(ab^3)= | | 0.667(6x-15)=0.75(8x+12) | | 5r-13-6r=3(r+5)-16 | | x+15=0 | | -3(4+h)+3h=9-6(h+7) |